Functional factor analysis in sesame under water - limiting stress: New concept on an old method - Mansouri, Sadollah; Najafabadi, Masood Soltani; Esmailov, Maghsadollah; Aghaee, Mostafa (Plant Breeding and Seed Science, 2014)
Multivariate statistical analysis, through their ability to extract hidden relationship between various traits, has a wide application in breeding programs. Having physiological concept on the multivariate analysis, factor analysis was used to extract differential relationships between different components involving in assimilate partitioning in sesame under regular irrigation regime and limited irrigation. The analysis revealed that under regular irrigation regime, the stored and/or currently produced assimilates are allocated to the filling seeds. However, incidence of water shortage in the beginning of flowering time make shifts in assimilate partitioning from formation of new seeds or capsules to the not-matured pre-formed seeds, which results in seeds with more nutrient storage. This indicates the requirement for change in breeding strategies under sub-optimal condition. The possible common language between factor concept in multivariate analysis, QTLs in genetics, and transcription factors in molecular biology is indicated.